Identification and Verification of Differential Display cDNAs Using Gene-Specific Primers and Hybridization Arrays. (June 1998) - Martin, K.J.; Kwan, C.-P.; O'Hare, M.J.; Pardee, A.B.; Sager, R.
An accurate and streamlined approach to differential display (DD) band identification and verification is described. To minimize false positives, the strategy avoids the use of impure Northern blot probes obtained from PCR-amplified DD bands. To increase throughput, the cloning of DD bands is replaced by a gene-specific primer approach, and hybridization arrays are used in place of Northern blots. In summary, DD bands obtained with long primers were directly sequenced to allow the design and synthesis of gene-specific primers, which were then used to PCR-amplify homogeneous probes for the verification of expression patterns by hybridization array analysis. Differential expression of 60 of the 63 genes tested was confirmed. Thus, false positives are not inherent to DD. The results demonstrate the power of DD used with hybridization arrays to rapidly generate information on expression patterns of differentially expressed genes.